Phenotypic variability in xeroderma pigmentosum group G: An uncommon case with severe prenatal‐onset Cockayne syndrome features. Issue 3 (11th May 2018) - Ricotti, R.; Nardo, T.; Striano, P.; Stefanini, M.; Orioli, D.; Botta, E.
Abstract :